Simultaneous Intake of β-Glucan and Plant Stanol Esters Affects Lipid Metabolism in Slightly Hypercholesterolemic Subjects - Theuwissen, Elke; Mensink, Ronald P (The Journal of nutrition, 2007)
Intake of food products rich in water-soluble fiber β-glucan and products enriched with plant stanol esters lower serum cholesterol. Combining 2 functional food ingredients into one food product may achieve additional reductions of serum cholesterol. Our objective was to investigate the effects of a simultaneous intake of β-glucan plus plant stanol esters on lipid metabolism in mildly hypercholesterolemic volunteers. In a randomized, controlled, 3-period crossover study, 40 mildly hypercholesterolemic men and women received muesli in random order twice a day for 4 wk, which provided, in total, 5 g control fiber from wheat (control muesli), 5 g oat β-glucan (β-glucan muesli), or 5 g oat β-glucan plus 1.5 g plant stanols (combination muesli). β-Glucan muesli decreased serum LDL cholesterol by 5.0% compared with control muesli (P = 0.013). Combination muesli reduced LDL cholesterol by 9.6% compared with control muesli (P < 0.001), and by 4.4% compared with β-glucan muesli (P = 0.036). Serum HDL cholesterol and triacylglycerol concentrations did not differ after the 3 treatments. Compared with control muesli, β-glucan muesli increased bile acid synthesis (P = 0.043) and decreased cholesterol absorption (P = 0.011). Addition of plant stanols did not influence bile acid synthesis but decreased cholesterol absorption (P < 0.001) and raised cholesterol synthesis (P = 0.016) compared with control muesli, and the plant stanols decreased cholesterol absorption compared with β-glucan muesli (P = 0.004). The combination muesli decreased serum concentrations of sitostanol compared with control muesli (P = 0.010). Plasma concentrations of lipid-soluble antioxidants did not differ after the 3 treatments. β-Glucan muesli effectively lowered serum LDL cholesterol concentrations. The addition of plant stanol esters to β-glucan-enriched muesli further lowered serum LDL cholesterol, although effects were slightly less than predicted.